Antimicrobial activity and acting mechanism of Tegillarca granosa hemoglobin-derived peptide (TGH1) against Vibrio parahaemolyticus. (October 2020) - Yang, Shen; Dong, Yuting; Aweya, Jude Juventus; Xie, Tingyu; Zeng, Beibei; Zhang, Yueling; Liu, Guang-Ming
Abstract: Vibrio parahaemolyticus is a Gram-negative bacterium and the one of leading causal agent of human foodborne diseases such as gastroenteritis upon consumption of raw, or contaminated marine products. There is an increased interest in the use of antimicrobial peptides (AMPs) as alternative food preservatives to prevent foodborne diseases. In this study, bioinformatics tools were used to predict and screen AMPs derived from hemoglobin of blood clam ( Tegillarca granosa ). A novel AMP, T. granosa hemoglobin-derived peptide (TGH1), was identified and its antimicrobial effect and mechanism of action on V. parahaemolyticus was explored. The minimal inhibitory concentration (MIC) of TGH1 on V. parahaemolyticus was 12.5 μg/mL. Transmission electron microscopy (TEM) revealed that TGH1 kills bacteria by perforating the cell wall perforation and destroying integrity of the cell membrane. Similarly, laser confocal microscopy confirmed that TGH1 entered bacterial cells by aggregating on the cell surface to destroy the cell. In addition, TGH1 increased the inner-membrane permeability of V. parahaemolyticus in a concentration-dependent manner, as well as prevented biofilm formation. Moreover, TGH1 has 55.6% β-sheet (antiparallel) structure and has no cytotoxic effects on normal human hepatocytes. Thus, peptide TGH1 has good potential use and application in antimicrobial control of foodborne pathogens. Highlights: A novel AMP TGH1 in T. granosa was identified by bioinformatics prediction. TGH1 killed pathogens by cell wall perforation and cell membrane permeabilization. The secondary structure of TGH1 includes 55.6% β-sheet (antiparallel). TGH1 has no cytotoxic to human normal hepatocytes.